Simple Synthesis of Dimethyl Nitrobenzhydrylphosphonates and Heteroarylnitroarylacetonitriles via Vicarious Nucleophilic Substitution (VNS) Reaction - Mąkosza, Mieczysław; Bechcicka, Małgorzata; Wojciechowski, Krzysztof (Synthesis, 2021)
Acetals of dimethyl phenyl- and heteroaryl-α-hydroxymethanephosphonates were deprotonated to generate carbanions, which enter the vicarious nucleophilic substitution (VNS) of hydrogen in aromatic nitro compounds to form 4-nitrobenzhydrylphosphonates and α-heteroaryl-4-nitrobenzylphosphonates. Similarly acetals of cyanohydrins of heteroaromatic aldehydes (furfural and 2-formylthiophene) react to form heteroaryl 4-nitroarylacetonitriles. The anion of the hemiacetal of acetaldehyde is an efficient leaving group in the base-induced β-elimination step – the crucial step in the VNS reaction. The reaction selectively occurred at the para-position to the nitro group.
Keywords: arylmethanephosphonates; arylacetonitriles; carbanions; nitroarenes; acetals; vicarious nucleophilic substitution